Comparison of Pb, Cd, Zn and Cr content of some mineral concrete admixtures - BAYRAKTAR, Oguzhan Yavuz; TURKYILMAZ, Aydin; ISINKARALAR, Kaan; KAPLAN, Gokhan (GSC Online Press, 2025)
Today, the demand for urban areas due to population growth worldwide and migration from rural to urban areas increases the need for new residential areas and new housing construction. This need also increases the demand for concrete, which is an important raw material especially in the building sector and constitutes a significant portion of construction input costs. Therefore, studies on the use of various environmental wastes as concrete admixtures in order to both reduce the cost of concrete and to dispose of environmental wastes are gaining importance and many studies have been conducted on the subject in recent years. However, the lack of sufficient data on the chemical structure of concrete admixtures leads to a lack of information on the environmental impacts of construction activities as well as the health of people working in the sector. For these reasons, this study aimed to determine and compare the Pb, Cr, Cd and Zn contents of some materials used as concrete admixtures. As a result of the study, it was determined that these heavy metal contents can vary significantly on a material basis and can reach up to 37.36 ppm for Pb, 103.67 ppm for Cr, 446.18 ppm for Zn and 444.85 ppm for Cd. This result shows that workers in the sector working with these materials may face serious health problems. Therefore, it is necessary to take precautions by providing the necessary awareness.
Keywords: Chemical Content; Heavy metal; Admixture; Concrete